Formação profissional em Serviço Social: uma análise a partir dos cursos na modalidade de ensino à distância (EaD) no Tocantins - Lima, Rodrigo Mamédio de (Universidade Federal do Tocantins, 2022)
This Specialization Course Conclusion Paper seeks to publicize the discussion of Higher Education, highlighting the Social Work courses held in the state of Tocantins through the Distance Learning modality, focusing on Universidade Anhanguera (UNIDERP) and Universidade Paulista (UNIP), which in addition to offering the Social Service course through EaD, are the private Higher Education Institutions that had the most annual vacancies authorized by the Ministry of Education. As research object we have the “Distance Learning in the state of Tocantins”, research guided by the objectives: to analyze the guidelines that guide the pedagogical projects of the Social Work courses in the distance learning modality in the state of Tocantins; place the growth of Social Work courses in the distance education modality in Tocantins in the dynamics of the expansion of higher education in Brazil; identify if the pedagogical projects of Social Work courses in the distance education modality in the state of Tocantins are in accordance with the 1996 ABEPSS Curriculum Guidelines and point out the challenges and possibilities of professional training in Social Work in the reality of Tocantins. To carry out this work, the following research techniques were used: bibliographical research, responsible for presenting issues related to Distance Learning in the state of Tocantins, and document analysis, with emphasis on the resolutions that it has on this subject. We seek to make some considerations about the contemporary transformations of capital that directly reflect on education policy, especially in higher education. This research highlights the importance of the Ethical-Political Project and professional training in Social Work, highlighting the analysis of the 1996 ABEPSS Curriculum Guidelines and those of the Ministry of Education for undergraduate courses in Social Work in 2002, given the challenges in times of counter-reform. In addition, we seek to debate about professional training in Social Work based on the reality of the state of Tocantins, which, being the youngest in the federation, is not left out of the interests of large capital and large private educational enterprises, especially, those that offer courses through the distance learning modality. We seek to present some particularities regarding the state of Tocantins, as well as the expansion of EaD courses, the teaching methodology and curriculum organization of the UNIDERP and UNIP Social Service courses, ending with a brief contextualization of the challenges and possibilities for training in the respective course in reality from Tocantins. Finally, we emphasize that this debate does not end with the results of this exploratory research, since this is just the beginning for the deepening of the discussion and contribution to the Social Work area.